Ministry Of Finance Decree No. 176 of the Year 2023 On the Rules Enforcing the Provisions of Law No. 18 of the Year 2023 On Expediting the Date of Entitlement to the Periodic Raises, Granting a Special Raise to the Workers Non-Addressed by the Civil Service Law, Increasing the Additional Incentive Payable to the State Civil Servants, Giving a Special Grant to the Workers of the Public Sector Companies and Public Business Sector Companies, Increasing the Civil and Military Pensions, Amending Certain Provisions of Law No. 415 of the Year 1954 on Practicing the Medical Profession, Amending Certain Provisions of the Law Organizing the Affairs of the Members of the Medical Professions Working at the Entities Affiliated to the Ministry of Health and Population Non-Addressed by Special Laws or Regulations as Promulgated by Law No. 14 of the Year 2014, Amending Certain Provisions of the Social Insurance and Pensions Law Promulgated by Law No. 148 of the Year 2019, Amending Certain Provisions of Law No. 212 of the Year 2020 Amending Certain Provisions of the Education Law Promulgated by Law No. 139 of the Year 1981 and Law No. 103 of the Year 1961 on the Reorganization of Al Azhar and its Authorities and Establishing A Social Welfare Fund for the Teachers at the Educational Professions and their Assistants at the Ministry of Education, Technical Education and Al Azhar Al Sharif = وزارة المالية قرار رقم 176 لسنة 2023 بشأن قواعد تنفيذ أحكام القانون رقم 18 لسنة 2023 بتعجيل موعد استحقاق العلاوات الدورية ومنح علاوة خاصة لغير المخاطبين بقانون الخدمة المدنية وزيادة الحافز الاضافى للعاملين بالدولة وتقرير منحة خاصة للعاملين بشركات القطاع الخاص وقطاع الأعمال العام وزيادة المعاشات المدنية والعسكرية وتعديل بعض أحكام القانون رقم 415 لسنة 1954 فى شأن مزاولة مهنة الطب وتعديل بعض أحكام قانون تنظيم شئون أعضاء المهن الطبية للعاملين بالجهات التابعة لوزارة الصحة والسكان من غير المخاطبين بقوانين أو لوائح خاصة الصادر بالقانون رقم 14 لسنة 2014 وتعديل بعض أحكما قانون التأمينات الاجتماعية والمعاشات الصادر بالقانون رقم 148 لسنة 2019 وتعديل بعض أحكام القانون رقم 212 لسنة 2020 بتعديل بعض أحكام قانون التعليم الصادر بالقانون رقم 139 لسنة 1981 والقانون رقم 103 لسنة 1961 بشأن إعادة تنظيم الأزهر والهيئات التى يشملها وبإنشاء صندوق الرعاية الاجتماعية للمعلمين بالمهن التعليمية ومعاونيهم بالتربية والتعليم والتعليم الفنى والأزهر الشريف - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic